Virality is not enough when the audience misses the point: A content analysis of youtube comments on environmental documentary “Sexy Killers” - Ika karlina Idris,; Nuurrianti Jalli,; khan, M. Laeeq; Sunaryo, (Penerbit Universiti Kebangsaan Malaysia, 2023)
During the Indonesian presidential election campaign, a documentary on coal mining problems in Indonesia titled “ Sexy Killers” became viral and was highly engaged on YouTube in early 2019, attracting 36 million views and above 100,000 comments. The documentary also received mainstream media coverage and had such a far-reaching appeal that it swayed many voters into not voting in the election. Showing the impact of coal mining on Indonesia’s environment and its people, the documentary exposed networks of business owners and politicians who had stakes in the coal mining company. This research thus delves into understanding the public discourse, especially the high number of YouTube comments on the documentary. The analysis revealed that despite the documentary’s widespread popularity, the discussion within the comments did not focus on the environmental problems (72.9%). Most of the comments discussed the political campaign and presidential candidates (41.3%), instead of discussing the environmental impact of coal mining in Indonesia (13.9%). The research is valuable in highlighting the centrality of political debates dwarfing real environmental issues in Indonesia. Environment activists use documentary movies as one of their advocacy strategies, but it must be followed by audience engagement strategy to assure the discussions are still relevant to increase audience awareness on the issue.